113 CONCURRENT SURGICAL TREATMENT STRATEGY FOR SYNCHRONOUS ESOPHAGEAL CANCER AND HEAD AND NECK CANCER IN OUR INSTITUTION. (17th September 2021) - Shimada, Ayako; Tanaka, Motomu; Ishii, Satoru; Yamamoto, Yusuke; Oosaki, Masaumi; Nishijima, Wataru; Oomura, Kenji; Wakabayashi, Go
Abstract:  : Esophageal cancer patients have a high frequency to coincide with head and neck (H&N) cancer. We have corporated together with Otorhinolaryngology, H&N Surgery, and Plastic surgery department doctors for the treatment of synchronous esophageal and H&N cancer patients. The aim of this study is to analyze the treatment results and prognosis of synchronous esophageal and H&N cancer patients. Methods: From January 2014 to December 2019, 5 patients underwent concurrent surgical resection of synchronous esophageal and H&N cancer in our institution. We retrospectively reviewed the surgical outcomes and prognosis of these patients of synchronous esophageal and H&N cancer (HNEC group) and compared the results with 27 patients who had esophagectomy with 3 regional lymph node dissection during the same period (EC group). Results: The location of H&N cancers were pharynx/tongue; 4/1, and clinical stage was all Stage IV. The clinical stage of esophageal cancers was Stage 0/I/II/III; 1/1/2/1. All patients underwent video-assisted thoracic esophagectomy. The surgical procedures concurrently performed for the H&N cancer were pharyngolaryngectomy with free jejunum transfer for 3 patients, wide tongue and mandibular segment resection with mandibular reconstruction in 1 patient, and mandibular transection with radial forearm flap reconstruction in 1 patient. There was no significant difference in the frequency of postoperative complication between 2 groups. HNEC group tend to have shorter recurrence free survival compared to EC group (p = 0.051). Conclusion: H&N surgery with thoracotomy is a highly invasive surgery, however, it can be safely performed with local management. The risk of recurrence is high in H&N cancer patients, therefore it is important to move onto adjuvant therapy without delay. Paraenteral nutrition may be useful in management of these patients.